EFFECT OF ORGANIZATIONAL REPUTATION ON E-LOYALTY ON BLIBLI CONSUMERS IN JABODETABEK: THE ROLE OF E-TRUST AND E-SATISFACTION - Safira Janice Prasetyo; Margaretha Pink Berlianto (SEAN Institute, 2023)
The growth of the economy supported by technology has been generated in a shift from the conventional to the digital era, the impact is very much felt in the commercial world, where the emergence of e-commerce is one clear evidence of this shift. One of the e-commerce companies in Indonesia that became one of the pioneers was Blibli, where at first Blibli was one of the top three e-commerce sites in Indonesia, but unfortunately there was a decrease in the number of users which caused Blibli to experience stagnation while other e-commerce companies actually experienced an increase in the number of users. The stagnation is in part attributed to the low number of new users and Blibli's failure to retain existing users. Therefore, this study was conducted to find out the factors that caused Blibli's consumer loyalty to be low, where the main determinants taken into account are organizational reputation, e-trust, and e-satisfaction. This research was conducted quantitatively, using a questionnaire distributed online, with a total sample of 273 respondents obtained using non-probability sampling techniques and purposive sampling methods, the data obtained were then processed using the SmartPLS statistical application.